2004
DOI: 10.3354/meps284109
|View full text |Cite
|
Sign up to set email alerts
|

Why is Ulva intestinalis the only macroalga inhabiting isolated rockpools along the Swedish Atlantic coast?

Abstract: Ulva intestinalis (previously called Enteromorpha intestinalis)is the principal marine macroalga growing in isolated rockpools along the Swedish west coast. Given that this alga can take up HCO 3 -under the conditions of high pH and low concentrations of inorganic carbon (Ci) that it creates in those pools, we hypothesized that those conditions would be unfavourable for the photosynthetic performance of other algae such that they would not be able to grow in the same pools. This was tested by transferring 2 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 23 publications
(31 reference statements)
2
51
0
Order By: Relevance
“…in pools or lagoons) but, except in a few cases (Björk et al 2004, Beer et al 2006, Middelboe & Hansen 2007, such shifts have not been ascribed any importance as a controlling factor for photosynthesis and growth of species featuring e.g. inorganic carbon limitations in nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in pools or lagoons) but, except in a few cases (Björk et al 2004, Beer et al 2006, Middelboe & Hansen 2007, such shifts have not been ascribed any importance as a controlling factor for photosynthesis and growth of species featuring e.g. inorganic carbon limitations in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Some algae can cause drastic pH increases (Axelsson & Uusitalo 1988); in the case of Ulva spp., this may be because they release OH - (Drechsler & Beer 1991). Only recently was it recognised that such high pH values could, in turn, affect the photosynthetic performance of other algae (see Björk et al 2004 for Ulva intestinalis in isolated rockpools and Middelboe & Hansen 2007 for shallow macro-algal habitats). Also, seagrasses can increase the pH of the surrounding seawater; Invers et al (1997) showed a pH increase of up to 0.5 units in seagrass meadows, which negatively affected photosynthetic rates of 3 seagrasses (Posidonia oceanica, Cymodocea nodosa and Zostera noltii).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we did not find any inhibition of photosynthesis. When pH values are >9.0, photosynthesis of some species is more likely to be inhibited (Maberly 1990;Björk et al 2004). Zou et al (2004) indicated that inorganic carbon (Ci) affinity and photosynthetic rates at pH 9.0 were decreased in G. lemaneiformis.…”
Section: Discussionmentioning
confidence: 99%
“…In populations of Fucus vesiculosus in the Baltic Sea, pH was about 9 in summer (Pearson et al 1998). In dense floating macroalgae in a brackish coastal lagoon in the Ebro River Delta (NE Spain) maximum pH was 9 to 9.5 (Menendez et al 2001) and pH values as high as 9.8 to 10.1 have been reported from isolated rock pools in Sweden (Björk et al 2004). Even though pH has never been measured systematically and continuously in natural macroalgal habitats, these sporadic measurements suggest that pH occasionally is high.…”
Section: Introductionmentioning
confidence: 99%